Molecular characterisation of the Ubiquitin-specific protease 15 catalytic domain - Ward, Stephanie (2019)
Ubiquitin-specific protease (USP15) is an important regulator of cellular pathways including transforming growth factor β, innate immune responses, mitophagy and mRNA processing. USP15 has been identified a possible therapeutic target because of its involvement in oncogenic pathways and high levels of USP15 have been associated with tumorigenesis. USP15 belongs to the DU family of USPs, sharing its domain architecture with paralogue USP4, and the more distantly related USP11. No structural information was available for the catalytic domain of USP15. Mitoxantrone was previously shown to be a common inhibitor of USP11 and USP15, but the mechanism of action was unknown. In this thesis, mitoxantrone was used to promote the crystallisation the catalytic domain, allowing the first structural characterisation of the USP15 catalytic core. The structure revealed the canonical USP fold consisting of a finger, palm and thumb fold with a misaligned catalytic triad. In this unbound structure, the catalytic cysteine is located 10 Å from the catalytic histidine resulting in a misaligned catalytic triad. This configuration is unusual and has only been observed in USP7 so far. Furthermore, the ubiquitin binding channel was found to be open, facilitated by flexible active site loops. Moreover, the crystal structure revealed mitoxantrone binds to the S1’ binding site and biochemical analysis confirmed mitoxantrone competes with the proximal substrate resulting a decrease in USP15 deubiquitinating activity. Isothermal titration calorimetry experiments revealed USP15 binds ubiquitin with a lower affinity and displayed a different thermodynamic profile to its paralogue USP4. Structural comparisons identified residue differences in the Blocking Loop 2 region and sequential mutations in this loop confirmed the BL2 has a role in ubiquitin binding. Finally, a novel ubiquitin fusion with a C-terminal isopeptide bond mimic was developed, which can easily be produced recombinantly. USP15 was found to bind this ubiquitin variant with significantly greater affinity compared to ubiquitin and linear di-ubiquitin, providing binding data to support previous observations that USP15 prefers isopeptide bond linked ubiquitin chains.